Prevalensi Premenstrual Syndrome dan Premenstrual Dysphoric Disorder Siswi Asrama dan Non Asrama Pasca Covid-19 - Tri Kesuma Dewi; Shinta Arini Ayu; Indhit Tri Utami; Widiyono Widiyono (Universitas Malahayati, 2023)
ABSTRACT Premenstrual Syndrome (PMS) and Premenstrual Dysphoric Disorder (PMDD) are disorders that occur in adolescent girls every month. Symptoms that occur in PMS and PMDD will interfere with daily adolescent activities, and will even reduce their quality of life. In research, one of the factors associated with PMS and PMDD is stress. Teenagers who live in dormitories according to research have higher stress levels than non-dormitory students. This study aims to determine the difference in the prevalence of PMS and PMDD that occur in dormitory and non-dormitory students. This study used a quantitative descriptive method where data was taken at a time using a questionnaire. This study there is no difference in the prevalence of PMDD in dormitory and non-dormitory students, but the rate of PMS is higher in non-dormitory students. This study also found that the impact of PMS and PMDD can interfere with students' daily activities and can even reduce their quality of life. PMS and PMDD can occur in female students both living in dormitories and non-dormitories, health workers, especially those in the school environment, should be able to provide treatment for the symptoms of PMS and PMDD appears so that it does not interfere with the quality of life of female students. Keywords: PMS,PMDD, Teen,Dormitory,Non-dormitory ABSTRAK Premenstrual Syndrome (PMS) dan Premenstrual Dysphoric Disorder (PMDD) adalah gangguan yang terjadi pada remaja wanita setiap bulannya. Gejala yang terjadi pada PMS dan PMDD tersebut akan menganggu aktifitas remaja sehari-hari, bahkan akan menurunkan kualitas hidup mereka. Pada penelitian salah satu faktor yang berhubungan dengan PMS dan PMDD ini adalah stress. Pada remaja yang tinggal diasrama menurut penelitian memiliki tingkat stress yang lebih tinggi dibandingkan siswi yang non asrama. Penelitian ini bertujuan untuk mengetahui perbedaan prevalensi PMS dan PMDD yang terjadi di siswi asrama dan non asrama. Penelitian ini menggunakan metode deskriptif kuantitatif dimana data diambil dengan sekali waktu menggunakan kuesioner. Pada penelitian ini tidak terdapat perbedaan prevalensi terjadinya PMDD pada siswi asrama dan non asrama, namun tingkat PMS lebih tinggi pada siswi non asrama. Penelitian ini juga menemukan bahwa dampak PMS dan PMDD dapat menganggu kegiatan siswi sehari-hari bahkan dapat menurunkan kualitas hidup mereka. PMS dan PMDD dapat terjadi pada siswi baik yang tinggal diasrama maupun non asrama, hendaknya tenaga kesehatan khususnya yang berada dilingkungan sekolah dapat memberikan penanganan terhadap gejala PMS dan PMDD yang muncul sehingga tidak menggangu kualitas hidup siswi. Kata Kunci: PMS,PMDD, Remaja,Asrama,Non-asrama